2011
DOI: 10.1128/jvi.01594-10
|View full text |Cite
|
Sign up to set email alerts
|

Hypervariable Region 1 Differentially Impacts Viability of Hepatitis C Virus Strains of Genotypes 1 to 6 and Impairs Virus Neutralization

Abstract: Hypervariable region 1 (HVR1) of hepatitis C virus (HCV) E2 envelope glycoprotein has been implicated in virus neutralization and persistence. We deleted HVR1 from JFH1-based HCV recombinants expressing Core/E1/E2/p7/NS2 of genotypes 1 to 6, previously found to grow efficiently in human hepatoma Huh7.5 cells. The 2a ⌬HVR1 , 5a ⌬HVR1 , and 6a ⌬HVR1 Core-NS2 recombinants retained viability in Huh7.5 cells, whereas 1a ⌬HVR1 , 1b ⌬HVR1 , 2b ⌬HVR1 , 3a ⌬HVR1 , and 4a ⌬HVR1 recombinants were severely attenuated. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
208
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 133 publications
(226 citation statements)
references
References 36 publications
14
208
1
3
Order By: Relevance
“…We found that whereas supernatant levels of HCV RNA and core protein were similar for HVR1-mutant and parental HCVcc (Fig. 2, A and B, left panels), either HVR1 modification had effects on HCVcc infectivity with a reduction of 40-fold for ⌬HVR1-HCVcc, consistently with previous reports (14,81), and 3-fold for L399R-HCVcc (Fig. 2C, left panel).…”
Section: Attachment Properties Of Hcvcc Subpopulations To Sr-bi-supporting
confidence: 80%
“…We found that whereas supernatant levels of HCV RNA and core protein were similar for HVR1-mutant and parental HCVcc (Fig. 2, A and B, left panels), either HVR1 modification had effects on HCVcc infectivity with a reduction of 40-fold for ⌬HVR1-HCVcc, consistently with previous reports (14,81), and 3-fold for L399R-HCVcc (Fig. 2C, left panel).…”
Section: Attachment Properties Of Hcvcc Subpopulations To Sr-bi-supporting
confidence: 80%
“…This supports the observation that polyclonal antibodies given postchallenge could control HCV infection only temporarily in the chimpanzee model (41). The infused NAbs might have prevented infection with heterologous 6a virus, and this was the strain previously found to be most efficiently neutralized in HCVcc assays (19,42).…”
supporting
confidence: 68%
“…Although they have an attenuated phenotype, most viruses lacking HVR1 remain infectious [14]. Furthermore, it has been proposed that this region obstructs the viral CD81 binding site as well as conserved neutralizing epitopes [14,15], potentially playing a role in some aspects of HCV immune evasion.…”
Section: Viral Particlementioning
confidence: 99%